The full employment interest rate implicit in classical economic theory - Cole, Nicolas D (Springer, 2022)
By including the rate of normal profit in a simple model of the macro-economy, the full employment interest rate is deduced to be 4½% at which Labor is not exploited by Capital. Criticisms by Marx and Keynes of the free-market economy were misdirected at Classical theory instead of the manipulation of interest rates by Central Banks to favour Capital over Labor.
Keywords: Rate of Normal Profit; Classical Theory; Central Banks; Full Employment Interest Rate